2022
DOI: 10.1021/acs.analchem.2c03089
|View full text |Cite
|
Sign up to set email alerts
|

3-Acetylpyridine On-Tissue Paternò–Büchi Derivatization Enabling High Coverage Lipid C═C Location-Resolved MS Imaging in Biological Tissues

Abstract: Unsaturated lipids containing single or more carbon–carbon double bonds (CC) within tissues are closely associated with various types of diseases. Mass spectrometry imaging (MSI) has been used to study the spatial distribution of lipid CC location isomers in tissue sections. However, comprehensive characterization of lipid CC location isomers using MSI remains challenging. Herein, we established an on-tissue charge-switching Paternò–Büchi (PB) derivatization method using 3-acetylpyridine (3-AP) as a react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Moreover, several MS techniques have been introduced to elucidate the carbon–carbon double bond in PC isomers, employing chemical-specific derivatization reactions such as the Paternò–Büchi photoreaction, epoxidation, and others. These approaches are aimed at enhancing the generation of fragments related to the position of the carbon–carbon double bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several MS techniques have been introduced to elucidate the carbon–carbon double bond in PC isomers, employing chemical-specific derivatization reactions such as the Paternò–Büchi photoreaction, epoxidation, and others. These approaches are aimed at enhancing the generation of fragments related to the position of the carbon–carbon double bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of chemical derivatization-coupled MS/MS bypasses the reaction required inside the mass analyzer. On-tissue or online derivatization was explored by a PB reaction, epoxidation, and singlet-oxygen reaction for MSI applications. These methods improve the sensitivity for detection of phospholipids and CC location isomers; however, due to a lack of capability to identify the chain composition, these methods cannot allocate CC locations onto the fatty acyl chain (e.g., PC 16:0_18:1­( n -9) or PC 16:0/18:1).…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to the structural diversity, more than 48 000 unique lipids are involved in the LIPID MAPS Structure Database, a considerable amount of which are isomers and isobars . Unsaturated lipids often exist in isomeric structures that differ only in the position of carbon–carbon double bonds (CC), the stereochemistry of CC ( cis / trans ) or stereospecific numbering ( sn ) positions, fulfilling different biological roles. , They are increasingly recognized as physiologically active molecules and promising lipid markers. , Recent works revealed that disruption of lipid homeostasis is associated with many disorders such as cancer, diabetes, and Alzheimer’s disease. …”
Section: Introductionmentioning
confidence: 99%